2021
DOI: 10.3389/fmicb.2021.628801
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Outer Membrane Vesicle Isolation Methods With an Escherichia coli tolA Mutant Reveals a Hypervesiculating Phenotype With Outer-Inner Membrane Vesicle Content

Abstract: Outer membrane vesicles (OMVs) produced by Gram-negative bacteria are mediators of cell survival and pathogenesis by facilitating virulence factor dissemination and resistance to antimicrobials. Studies of OMV properties often focus on hypervesiculating Escherichia coli mutants that have increased OMV production when compared to their corresponding wild-type (WT) strains. Currently, two conventional techniques, ultracentrifugation (UC) and ultradiafiltration (UF), are used interchangeably to isolate OMVs, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 77 publications
1
57
0
Order By: Relevance
“…We have previously shown that the overall protein composition of BMVs varies between different bacterial strains ( 7 ), throughout various stages of bacterial growth ( 4 , 45 ), and based on BMV size ( 29 ). It has also been shown that bacterial culture conditions ( 46 ) and methods of BMV isolation ( 34 , 47 ) can alter BMV protein composition. However, it is unclear whether there is variability in the overall quantity of proteins packaged into BMVs produced by different bacterial species and strains and the biological consequences of quantifying BMVs based on their variable protein cargo amounts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the overall protein composition of BMVs varies between different bacterial strains ( 7 ), throughout various stages of bacterial growth ( 4 , 45 ), and based on BMV size ( 29 ). It has also been shown that bacterial culture conditions ( 46 ) and methods of BMV isolation ( 34 , 47 ) can alter BMV protein composition. However, it is unclear whether there is variability in the overall quantity of proteins packaged into BMVs produced by different bacterial species and strains and the biological consequences of quantifying BMVs based on their variable protein cargo amounts.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a range of protein assays are used to quantify BMVs, including Bradford ( 28 , 29 ), bicinchoninic acid (BCA) ( 12 , 30 ), Lowry ( 31 ), or Qubit protein assays ( 32 , 33 ), with no single protein assay used as the standard method to quantify BMVs in the field. However, variables in BMV isolation ( 34 ), bacterial strains ( 35 ), culture conditions ( 36 ), growth stage ( 4 ), and BMV size ( 29 ) can all significantly alter BMV protein content, suggesting that BMV protein concentration may not directly correlate with BMV quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also report OMVs of larger sizes, aggregates, chains, and tubes [ 19 ]. However, there are no baselines for isolation methods; hence, the types, cargo, and specific functions of OMVs will vary from one species to another, making comparisons difficult [ 20 , 21 ]. We have yet to learn more about the species and strain-specific roles of OMVs of phytopathogenic bacteria in bacteria–bacteria and bacteria–host interactions, as well as their potential to control plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The easy programmability of bacteria and the many advancements in synthetic biology have enabled the development of OMVs packed with therapeutic recombinant proteins. To increase OMV yield, hypervesiculating strains can be developed by deleting or mutating genes such as the nlpI , tolR , and the mlaE gene or by overexpressing membrane proteases such as OmpT ( Premjani et al, 2014 ; Chen et al, 2016 ; Ojima et al, 2020 ; Reimer et al, 2021 ). The addition of tris-glycine to the bacterial culture media has also been shown to increase OMV production in vitro ( Hirayama and Nakao, 2020 ).…”
Section: Bacterial Extracellular Vesicles: Outer Membrane Vesicles-a Similar Facetmentioning
confidence: 99%